Digital Learning Media: Review - Menrisal (RADINKA JAYA UTAMA PUBLISHER, 2022)
Digital learning media is the use of technology in the form of software to distribute information (transfer of knowledge) to students. The purpose of using digital learning media is so that students can receive knowledge, skills, more easily, without being constrained by space and time. Digital learning systems require infrastructure and technology support, such as computers, internet access, servers, television, interactive video, CD/DVD ROM, and so on. Digital learning can be done in two ways, namely fully digital or in combination with face to face (face to face). Face to face can also be done by involving technology, such as video conferencing or tele conferencing. The success of developing a digital learning requires a gradual design. Digital design is known as storyboarding and visual mapping (visual map). This design is specifically focused on the use of advanced methods in digital learning, especially on the aspects of design and its principles.